1983
DOI: 10.1126/science.220.4596.477
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics and Science Learning: A New Conception

Abstract: Findings in cognitive science suggest new approaches to teaching in science and mathematics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
132
0
39

Year Published

1984
1984
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(174 citation statements)
references
References 7 publications
3
132
0
39
Order By: Relevance
“…A short paper published in Science last April (Resnick, 1983) asserts that "recent findings in cognitive science suggest new approaches to teaching in science and mathematics" (p. 477), but the examples given, when expressed in noncognitive style, are simply these: (a) Students learn about the world in "naive" ways before they study science; (b) naive theories interfere with learning scientific theories; (c) we should therefore teach science as early as possible; (d) many problems are not solved exclusively with mathematics; qualitative experience is important; (e) students learn more than isolated facts; they learn how facts are related to each other; and (f) students relate what they are learning to what they already know. If these are recent findings, where has cognitive science been?…”
Section: Psychological Roadblocksmentioning
confidence: 99%
“…A short paper published in Science last April (Resnick, 1983) asserts that "recent findings in cognitive science suggest new approaches to teaching in science and mathematics" (p. 477), but the examples given, when expressed in noncognitive style, are simply these: (a) Students learn about the world in "naive" ways before they study science; (b) naive theories interfere with learning scientific theories; (c) we should therefore teach science as early as possible; (d) many problems are not solved exclusively with mathematics; qualitative experience is important; (e) students learn more than isolated facts; they learn how facts are related to each other; and (f) students relate what they are learning to what they already know. If these are recent findings, where has cognitive science been?…”
Section: Psychological Roadblocksmentioning
confidence: 99%
“…Dickson, Brown ve Gibson (1984) ve Resnick (1983) çalışmalarında, öğrencilerin çıkarma işleminde en çok küçük sayılardan büyük sayıları çıkarırken zorluk yaşadıklarını ifade etmişlerdir. Araştırmacılar bu hatayı, çıkarmaya ilk geçişte öğrencinin sürekli büyük sayıdan küçük sayıyı çıkarması gerektiğini düşünmesi ile ilişkilendirmişlerdir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Wenglinsky (1998) found evidence that using technology can support mathematics learning but contends that constructivist applications had a more positive effect on math achievement than traditional uses of drill and practice software. Additionally, research has shown that teaching students mathematics conceptually rather than algorithmically leads to a deeper understanding of the content (Resnick, 1983;Kilpatrick, 2001;Ogbuehi, 2007). This deep conceptual understanding of elementary and middle school mathematics content is crucial for students to be successful in high school mathematics and beyond (Kilpatrick, 2001).…”
Section: The Role Of Technology In Teachingmentioning
confidence: 99%